Whole genome sequencing confirms source of pathogens associated with bacterial foodborne illness in pets fed raw pet food. (March 2019) - Jones, Jennifer L.; Wang, Leyi; Ceric, Olgica; Nemser, Sarah M.; Rotstein, David S.; Jurkovic, Dominika A.; Rosa, Yamir; Byrum, Beverly; Cui, Jing; Zhang, Yan; Brown, Cathy A.; Burnum, Anne L.; et al.
Reports of raw meat pet food containing zoonotic foodborne bacteria, including Salmonella, Escherichia coli, and Listeria monocytogenes, are increasing. Contaminated raw pet food and biological waste from pets consuming those diets may pose a public health risk. The U.S. Food and Drug Administration Veterinary Laboratory Investigation and Response Network conducted 2 case investigations, involving 3 households with animal illnesses, which included medical record review, dietary and environmental exposure interviews, animal sample testing, and whole genome sequencing (WGS) of bacteria isolated from the pets and the raw pet food. For each case investigation, WGS with core genome multi-locus sequence typing analysis showed that the animal clinical isolates were closely related to one or more raw pet food bacterial isolates. WGS and genomic analysis of paired animal clinical and animal food isolates can confirm suspected outbreaks of animal foodborne illness.